2008
DOI: 10.1128/jvi.00734-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of CD1d in Neurotropic Virus Infection

Abstract: The GDVII strain of Theiler's murine encephalomyelitis virus (TMEV) causes an acute fatal polioencephalomyelitis in mice. Infection of susceptible mice with the DA strain of TMEV results in an acute polioencephalomyelitis followed by chronic immune-mediated demyelination with virus persistence in the central nervous system (CNS); DA virus infection is used as an animal model for multiple sclerosis. CD1d-restricted natural killer T (NKT) cells can contribute to viral clearance and regulation of autoimmune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…Teixeira, and F. Trottein, submitted for publication) infections. Studies using CD1d-deficient mice, which not only lack iNKT cells but also non-iNKT cells, have suggested that NKT cells (either iNKT cells, non-iNKT cells, or both) positively contribute to the immune response to respiratory syncytial virus (20), encephalomyocarditis virus (21), murine CMV (22), and Theiler's murine encephalomyelitis virus (23). In contrast, noniNKT cells are rather deleterious during coxsackievirus infection (24).…”
mentioning
confidence: 99%
“…Teixeira, and F. Trottein, submitted for publication) infections. Studies using CD1d-deficient mice, which not only lack iNKT cells but also non-iNKT cells, have suggested that NKT cells (either iNKT cells, non-iNKT cells, or both) positively contribute to the immune response to respiratory syncytial virus (20), encephalomyocarditis virus (21), murine CMV (22), and Theiler's murine encephalomyelitis virus (23). In contrast, noniNKT cells are rather deleterious during coxsackievirus infection (24).…”
mentioning
confidence: 99%
“…CD1d-dependent cells are involved in controlling the infection in the CNS, as shown by the higher viral load in Cd1d À/À mice. This increased viral load is probably due to a defective local immune response, as few infiltrating immune cells are detected in the CNS of Cd1d À/À mice [47]. Interestingly, studies of CD1d-deficient mice suggest that NKT cells could modulate the IFN-g/IL-4 balance during infection with the TMEV DA strain, which induces acute disease followed by chronic immune-mediated demyelination with virus persistence in the CNS.…”
Section: Theiler's Murine Encephalomyelitis Virus (Tmev)mentioning
confidence: 99%
“…However, with the increase in the number of immunocompromised individuals, whether through increasing populations of AIDS patients or pharmacologically compromised tissue transplant recipients, there has been a concomitant increase in viral encephalitis (11,77). Some viral infections, rather than being cleared by the host's immune system, result instead in high morbidity or mortality, often accompanied by severe inflammation (18,68,81). The balance between whether the adaptive immune response to a specific viral infection is protective or harmful is delicate, as many of the mechanisms that mediate inflammation in the CNS in both settings are similar (6,12,31,65).…”
Section: Genetic Studies With Immunocompetent Mice Show the Importancmentioning
confidence: 99%